Endophytic Bacteria from Faloak Plant Seed (Sterculia comosa) as Antibacterial Agent - Maria Yasinta Moi; Endang Kusdiyantini; Sri Pujiyanto (Biosaintifika: Journal of Biology & Biology Education, 2018)
Endophytic bacteria isolated from some various kind of plants are able to yield some active compounds which have a role as an antibacterial compound. This work aimed to isolate and to screen the Endophytic bacteria from Faloak seed in its charge in inhibiting two kinds of pathogenic bacteria, Staphylococcus aureus and Escherichia coli. There were six isolates of Endophytic bacteria isolated in this work. According to the screening result, one isolate which had the most potential antibacterial activity (marked by the formation of inhibition zone) against S. aureus and E. coli. That most potential isolate was then tested and identified for both biochemical properties and molecular 16S rRNA gene. The result of this study showed that the endophytic bacteria isolate of Faloak seed with the code of S1 had the similarity with Enterobacter xiangfangensis strain 10-17 by 93 %. The research about endophytic bacteria of Faloak plants was never conducted before. Thus this research was expected to give information about the potential of antimicrobial ability Faloak plants which can be utilized in the discovery of new antibiotic compounds which in the future are expected to overcome the problem of microorganism resistance to antibiotics. The use of endophytic bacteria is expected to prevents the extinction of Faloak plants due to excessive use.